2004
DOI: 10.1177/10983007040060010401
|View full text |Cite
|
Sign up to set email alerts
|

Using Staff and Student Time Engaged in Disciplinary Procedures to Evaluate the Impact of School-Wide PBS

Abstract: This article presents an example of how school time was monitored to facilitate a cost analysis of school-wide systems of positive behavior support (PBS). The article provides descriptions of how (a) PBS efforts were initiated in the school, (b) time and money were spent preparing for and implementing PBS, and (c) changes in behavior referrals and suspension were used to evaluate the effect of PBS on the larger system. The results indicated a positive assessment of PBS based on predetermined criteria. The disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 20 publications
1
85
0
Order By: Relevance
“…Office discipline referral data are commonly used as (a) an indicator of school climate, (b) a measure of the effectiveness of SWPBS implementation (Irvin, Tobin, Sprague, Sugai, & Vincent, 2004), and (c) a mechanism for determining the behavioral support needs of the school (Irvin et al, 2006;Scott & Barrett, 2004). The mean ODRs for this study were adjusted to provide consistent metrics for measuring impact across sites by using the total ODRs per day, per month, per 100 students, and per average daily enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Office discipline referral data are commonly used as (a) an indicator of school climate, (b) a measure of the effectiveness of SWPBS implementation (Irvin, Tobin, Sprague, Sugai, & Vincent, 2004), and (c) a mechanism for determining the behavioral support needs of the school (Irvin et al, 2006;Scott & Barrett, 2004). The mean ODRs for this study were adjusted to provide consistent metrics for measuring impact across sites by using the total ODRs per day, per month, per 100 students, and per average daily enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…For example, each disciplinary action for a student requires up to 20 minutes of the instructor's time. The period for addressing a discipline referral goes up to 45 minutes for administrators (Scott & Barrett, 2004). Over time, responding to discipline results in lost educational experience for students.…”
Section: Academic and Behaviour Problems In Secondary Schoolsmentioning
confidence: 99%
“…For instance, ensuring that school personnel are aware of the potential benefits of PBS (Luiselli et al, 2005;Metzler et al, 2001;Netzel & Eber, 2003;Oswald et al, 2005;Scott, 200 I) and including staff members in action-plan development (Oswald et al;Scott;Turnbull et al , 2002) can achieve staff buy-in. Using existing sources of data, such as referral and suspension data, makes data collection and data-based decision making easier (Luiselli et al;Scott & Barrett, 2004). Researchers have identified a number barriers to PBS implementation (Lohrman, Forman, Martin, & Palmieri, 2008).…”
Section: Overcoming Barriersmentioning
confidence: 99%
“…In addition to demonstrating a reduction in behavioral problems, Scott and Barrett (2004) examined the impact of reduced disciplinary problems on instructional time. They found that following PBS implementation, students experienced many more hours of instruction because less student time was spent in exclusionary punishment and less teacher time was spent addressing behavioral concerns.…”
Section: Benefits Of Pbs Implementationmentioning
confidence: 99%